2020
DOI: 10.1177/09708464211038717
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of MSME’s Efficiency: A Study of Two Comparable Northern Indian Regions

Abstract: Jammu and Kashmir (J&K) and Himachal Pradesh (HP) are the two northern states of the Indian union. The two neighbouring states are mountainous and backward as compared to the rest of the country. Of the two, J&K has more natural resources and population. On the contrary, HP, over time, has demonstrated higher outcomes in terms of basic indicators, gross state domestic product (GSDP) and economic growth. This article examines these two economies and attempts to compare them on the basis of their respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The technology purchased by this unit is considered to be state of the art and is the most sophisticated cold-store unit located in J&K. Interestingly, some of the units under study are actively carrying out firm-specific research and development. Studies like Majeed et al (2021) validate the fact that the firm-specific research and development in India is very much limited. However, given the levels of investments that go into the setting up of the cold-store units and the level of R&D and technology utilised, innovation and R&D at the firm level find serious grounds.…”
Section: Resultsmentioning
confidence: 79%
See 3 more Smart Citations
“…The technology purchased by this unit is considered to be state of the art and is the most sophisticated cold-store unit located in J&K. Interestingly, some of the units under study are actively carrying out firm-specific research and development. Studies like Majeed et al (2021) validate the fact that the firm-specific research and development in India is very much limited. However, given the levels of investments that go into the setting up of the cold-store units and the level of R&D and technology utilised, innovation and R&D at the firm level find serious grounds.…”
Section: Resultsmentioning
confidence: 79%
“…The average number of employees in a cold-store unit of J&K is 144. Comparing it with a number of studies like Majeed et al (2021), it can be concluded that the cold-store units have a huge employment generation potential as compared to the rest of the indigenous and local industries. The supervisors of the cold-store units are not the entrepreneurs but the technical and skilled staff that run the machinery.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Studies like Majeed et al (2021a) have already validated the fact that the industrialization process in the region of J&K is dominated by the Micro, Small and Medium Enterprises (MSMEs, henceforth). Neither the ASI data under study nor any other source validates the existence and presence of large units or multinational corporations in the region.…”
Section: Resultsmentioning
confidence: 99%